THE EFFECTS OF KEFIR ON THE INFLAMATORY STATUS AND THYROID FUNCTION (EXPERIMENTAL STUDY ON WISTAR RATS AFTER EXPOSED TO CHLORPYRIFOS) - Rasipin, Rasipin; Dharmana, Edi; Hadisaputro, Suharyo; ., Suhartono (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Goiter is an enlarged thyroid gland remained a health problem in the agricultural areas. Chlorpyrifos (CPF) is a pesticide widely used by farmers. Previous studies proved that CPF exposure caused thyroid dysfunction. The objective of this study was to evaluate the effects of kefir on the inflammatory status and thyroid function in male Wistar rats after exposed to CPF using biochemical and histopathological assays. Methods: Male rats were divided into 4 groups, i.e., CPF 5+kefir (5 mg/kg+3.6 ml/200 g, respectively), CPF 5 (5 mg/kg), corn oil (CO 1 ml/200 g), and negative control (NC: Without CPF, CO, and kefir). Results: Kefir supplementation dose 3.6 ml/200 g once a day for 28 days in the rats after exposed to CPF dose 5 mg/kg once a day for 14 days, in CPF 5+kefir as compared to CPF 5: Significantly (p<0.05) decreased serum tumor necrosis factor-Î± (TNF-Î±) level; significantly (p<0.01) maintained serum levels of tumor growth factor-Î² (TGF-Î²) and thyroid stimulating hormone (TSH) not to decrease; not significant (p>0.05) decreased the level of interleukin-1Î², cluster of differentiation-26 expression and level of T4 serum; not significant (p>0.05) maintained the level of anti-thyroid peroxidase not to decrease; and not significant (p>0.05) increased the apoptosis index. This study suggests that CPF exposure causes the inflammatory process which leads to thyroid dysfunction. Conclusion: Kefir supplementation significantly decreased the level of TNF-Î± and maintained the levels of TGF-Î² and TSH not to decrease, possible to reduce the inflammatory and thyroid dysfunction processes caused by exposure to CPF in experimental animals. Keywords: Kefir, Chlorpyrifos, Inflammation, Thyroid function.